Inverse design of glass structure with deep graph neural networks - Qi Wang (Nature Portfolio, 2021)
The inverse design of the material for given target property is challenging for glasses due to their disordered non-prototypical structure. Wang and Zhang propose a data-driven property oriented inverse approach for design of glassy materials with desired functionalities.